2016
DOI: 10.1186/s12913-016-1482-7
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of asthma and chronic obstructive pulmonary disease and the impact of poor inhalation technique with commonly prescribed dry powder inhalers in three European countries

Abstract: BackgroundAsthma and chronic obstructive pulmonary disease (COPD) are common chronic inflammatory respiratory diseases, which impose a substantial burden on healthcare systems and society. Fixed-dose combinations (FDCs) of inhaled corticosteroids (ICS) and long-acting β2 agonists (LABA), often administered using dry powder inhalers (DPIs), are frequently prescribed to control persistent asthma and COPD. Use of DPIs has been associated with poor inhalation technique, which can lead to increased healthcare resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 46 publications
4
68
0
4
Order By: Relevance
“…Classic randomized control trials investigating the efficacy of inhaler devices tend to enrol very selective groups of patients . In real‐life practice setting, factors such as imperfect inhalation techniques and non‐adherence to treatment are common, negatively impacting inhaler treatment outcomes . The current study indicated that within Korean real‐life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Classic randomized control trials investigating the efficacy of inhaler devices tend to enrol very selective groups of patients . In real‐life practice setting, factors such as imperfect inhalation techniques and non‐adherence to treatment are common, negatively impacting inhaler treatment outcomes . The current study indicated that within Korean real‐life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique.…”
Section: Discussionmentioning
confidence: 79%
“…11,17,18 In real-life practice setting, factors such as imperfect inhalation techniques and non-adherence to treatment are common, [18][19][20][21][22] × strength Categorized as 0, >0 to ≤250, >250 to ≤500, >500 μg daily ICS dosage (low, medium and high as per GINA guidelines) Oral thrush Diagnostic code for oral thrush OR Prescription of antifungal therapy negatively impacting inhaler treatment outcomes. 17,[22][23][24][25] The current study indicated that within Korean real-life practice setting, pMDI was comparable to DPI in preventing asthma exacerbations, and led to better asthma control, despite the potential for imperfect adherence and inhaler technique. In addition, while this study was retrospective in nature, data were collected prospectively and thus the patients were not influenced by recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhaler technique errors have been associated with uncontrolled asthma as well as increased rates of severe COPD exacerbations [5][6][7]. Ultimately, poor inhalation technique leads to increased healthcare utilization and costs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lewis et al [33,34] analysed the group of patients who were using inhaled glucocorticosteroids (GCS) and long-acting beta-2 agonists (LABA) with the popular DPI: Turbuhaler ® (budesonide + formoterol) or with Accuhaler ® (Disc) (fluticasone propionate + salmeterol) for one year in several European countries. The study published in the year 2016 supplied many practical conclusions [33]. Firstly, it was showed that the inappropriate technique of inhalation with the DPI significantly increases the risk of hospitalisation, visits to the emergency room, antibiotic therapy or the use of oral GCS (by 47%, 62%, 50% and 54% respectively) ( Table 2).…”
Section: Medical Leave 47%mentioning
confidence: 99%